2003
DOI: 10.1097/00001813-200303000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of doxorubicin administered i.v. as Myocet (TLC D-99; liposome-encapsulated doxorubicin citrate) compared with conventional doxorubicin when given in combination with cyclophosphamide in patients with metastatic breast cancer

Abstract: Myocet (TLC D-99) is a liposomal formulation of the anti-neoplastic drug doxorubicin with an improved therapeutic index compared with conventional doxorubicin. The objective of this study was to assess the plasma disposition of doxorubicin when administered i.v. as TLC D-99 and to compare this to conventional drug. Metabolite (doxorubicinol) plasma levels were also quantitated in both treatment groups. Plasma was collected during the first course of treatment from 10 patients receiving TLC D-99 60 mg/m and 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(58 citation statements)
references
References 16 publications
2
54
0
2
Order By: Relevance
“…4 Doksorubisinin ilaç taşıyıcı sistemlerden birisi olan lipozomlarla birleştirilmesiyle farmakokinetik ve toksik özellikleri değişmektedir. 5 Lipozomal doksorubisin alan hastalarda gelişen mukokütanöz yan etkilerin klinik özelliklerinin değerlendirildiği ça-lışmamızda en sık, "el-ayak sendromu" olarak da bilinen, akral eritrodisestezi izlendi. Akral eritrodisestezi, iki ya da üç kür kemoterapi sonrasında ortaya çıkıp, dört hastada evre III şiddetteki lezyonlarla seyretmekteydi.…”
Section: Discussionunclassified
“…4 Doksorubisinin ilaç taşıyıcı sistemlerden birisi olan lipozomlarla birleştirilmesiyle farmakokinetik ve toksik özellikleri değişmektedir. 5 Lipozomal doksorubisin alan hastalarda gelişen mukokütanöz yan etkilerin klinik özelliklerinin değerlendirildiği ça-lışmamızda en sık, "el-ayak sendromu" olarak da bilinen, akral eritrodisestezi izlendi. Akral eritrodisestezi, iki ya da üç kür kemoterapi sonrasında ortaya çıkıp, dört hastada evre III şiddetteki lezyonlarla seyretmekteydi.…”
Section: Discussionunclassified
“…After i.v. administration in MBC patients, Myocet may slow blood clearance and reduce the distribution volume of the encapsulated agents in comparison with the aqueous formulation (Swenson et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…First, it is well known that both prolonging the duration and elevating the concentration of ADR enhances its cytotoxic efficacy (Rupniak et al 1983). Swenson et al (2003) reported that compared with conventional ADR, Myocet substantially slowed the blood clearance and improved the plasma concentrations of total ADR after i.v. administration.…”
Section: Discussionmentioning
confidence: 99%
“…Myocet Ò was developed to selectively reduce the release of active doxorubicin in normal tissues while increasing its concentration in tumor tissues, with the aim of reducing toxicity and increasing efficacy [12,[14][15][16]. Because of their size, the liposomes do not pass through the capillary beds of normal tissues while they readily diffuse through the chaotic and highly permeable capillaries of tumors.…”
Section: Introductionmentioning
confidence: 99%